2003
DOI: 10.1046/j.1528-1157.2003.33002.x
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Significance of Video‐EEG Monitoring Findings on Pseudoseizure Patients Differs Between Neurologists and Psychiatrists

Abstract: Summary:Purpose: The diagnosis of psychogenic pseudoseizures has improved with the availability of video-electroencephalography (EEG) monitoring; however, the outcome of this difficult disorder has remained poor. In an attempt to elucidate factors contributing to this poor outcome, we hypothesized that neurologists and psychiatrists differ in their views of the diagnosis and management of psychogenic pseudoseizure patients.Methods: The hypothesis was tested by using a brief anonymous questionnaire administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 10 publications
0
33
0
4
Order By: Relevance
“…Previous research on psychogenic non-epileptic seizures (PNES) have shown that there is a significant difference in opinions regarding EEG results between psychiatrists and neurologists. In a study by Harden et al (2003) psychiatrists were found to have a lot less confidence in EEG results and accuracy in aiding the diagnosis of psychogenic symptoms than neurologists.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on psychogenic non-epileptic seizures (PNES) have shown that there is a significant difference in opinions regarding EEG results between psychiatrists and neurologists. In a study by Harden et al (2003) psychiatrists were found to have a lot less confidence in EEG results and accuracy in aiding the diagnosis of psychogenic symptoms than neurologists.…”
Section: Discussionmentioning
confidence: 99%
“…Among neurologists, the inter-rater reliability for video-EEG diagnosis of PNES is only moderate. 58 When the disciplines of Neurology and Psychiatry were surveyed with regard to how much they “believed” the v-EEG diagnosis of PNES, 70% of neurologists, but only 18% of psychiatrists, answered “most of the time.” 59 There is certainly a need to “build bridges” between these disciplines and, in particular, to educate mental health professionals in order to help patients be properly diagnosed and receive the timely treatment they need.…”
Section: Challenges In the Management Of Pnesmentioning
confidence: 99%
“…It ensures an unambiguous, consistent, and databased message. It limits misunderstanding that can occur when dealing with somatoform illnesses and keeps patients, family, and providers all "on the same page" (Harden, Burgut, & Kanner, 2003 ). Questions requiring medical and psychological expertise can be answered together.…”
Section: Reporting the Findingsmentioning
confidence: 99%